2018
DOI: 10.1016/j.toxrep.2018.08.014
|View full text |Cite|
|
Sign up to set email alerts
|

Improved effect of pumpkin seed oil against the bisphenol-A adverse effects in male mice

Abstract: The present study was conducted to evaluate the ameliorative role of pumpkin seed oil (PSO) against potential adverse effects of bisphenol-A (BPA) in male mice. BPA was administered to the mice orally at a dose of 50 mg/kg body weight once a day for 28 successive days. While, PSO was administered to the mice orally at 1 mL/kg b w either before, with or after treatment of BPA, once a day for 28 successive days. The studied parameters were DNA damage evaluation using comet assay in liver and testes cells and mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…The histopathological alterations due to BPA exposure could also be another factor affecting the negative changes in semen quality. Previous studies reported similar results that BPA could cause necrosis, seminiferous tubule degenerations or aplasia and giant cell formation (10). BPA increased the number of apoptotic cells in the seminiferous tubules (41).…”
Section: Tab 1 Effects Of Oral Bisphenol a (Bpa) Administration On supporting
confidence: 57%
“…The histopathological alterations due to BPA exposure could also be another factor affecting the negative changes in semen quality. Previous studies reported similar results that BPA could cause necrosis, seminiferous tubule degenerations or aplasia and giant cell formation (10). BPA increased the number of apoptotic cells in the seminiferous tubules (41).…”
Section: Tab 1 Effects Of Oral Bisphenol a (Bpa) Administration On supporting
confidence: 57%
“…There are studies that focus on the health properties of pumpkin seed oil. Other studies involving animals have shown that pumpkin seed oil protects against the genotoxicity caused by bisphenol A and azathioprine [30,31]. It was also found that pumpkin seed oil is characterized by antihypertensive and cardioprotective effects.…”
Section: Introductionmentioning
confidence: 98%
“…It has been shown that DNA damage could reduce the success of in vitro fertilization (IVF) (Wdowiak et al, 2015) and intracytoplasmic sperm injection (ICSI) (Avendaño et al, 2010), weakens pregnancy (Carlini et al, 2017), and even affects the offspring's health (Jin et al, 2015). Comparative studies of spermatozoa from clinical patients and laboratory animals found that BPA may be associated with declined semen quality and increased sperm DNA damage (Toyama & Yuasa, 2004;Meeker et al, 2010;Vitku et al, 2016;Fawzy et al, 2018;Omran et al, 2018). However, the underlying mechanism for the impacts of BPA on sperm DNA damage is still unclear.…”
Section: Introductionmentioning
confidence: 99%